Dihuang Yinzi, a Classical Chinese Herbal Prescription, for Amyotrophic Lateral Sclerosis: A 12-Year Follow-up Case Report. Issue 14 (April 2016) - Qiu, Hui; Li, Ji-huang; Yin, Su-bing; Ke, Jiang-qiong; Qiu, Chang-lin; Zheng, Guo-qing
Abstract : Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating progressive neurodegenerative disease with no effective treatment and death within 2 to 5 years after symptom onset. Here, we reported a case of ALS patient using modified Dihuang Yinzi (DHYZ), a classical traditional Chinese medicine (TCM) prescription, who has survived 12 years with significant improvement in bulbar paralysis. A 41-year-old Chinese Han nationality woman was admitted to the hospital with complaints of weakened bilateral grip, slurred speech, stumbling, and muscle twitching for 3 years. The electromyography showed neurogenic injury in bilateral upper limbs and tongue. She was diagnosed with ALS according to the revised El escorial criteria. The patient was orally administrated with Riluzole 100 mg daily for 10 months and then stopped. Subsequently, she resorted to TCM. Based on the TCM theory, the patient was diagnosed with Yinfei syndrome because of kidney deficiency. DHYZ was chosen because it has the function of replenishing kidney essence to treat Yinfei syndrome. Up to now, she has been using modified DHYZ continuously for 12 years. The patient survived with ALS and did not require permanent continuous ventilator. In addition, the symptoms of choking on liquids are improved, and the utility of 30 mL water swallow test was improved with grade 2. The symptoms of muscle fibrillations of limbs are also reduced. However, muscle strength worsened slowly. The repeated electromyography showed motor conduction amplitude reducing gradually and velocity not changing more when compared with the initial electromyography. Our findings suggested that DHYZ can be potentially used in ALS patients because of its multi-targeted neuroprotection and general safety, although ALS does not have a cure. In addition, we identified the area that is worthy of further study and DHYZ as a promising candidate for further clinical application and ALS trials. Rigorous randomized controlled trials are needed in the future.